(untitled) (Third Sector Social Economic Review, 2022)
Oil and natural gas are important in meeting energy needs. The intensive use of fossil fuels is responsible for the depletion of scarce resources and also emits harmful gases. Due to the government’s taxation on gasoline and diesel vehicles, the consumption of limited resources and the increasing environmental awareness including the preferences of individuals and manufacturers, have led to increasing interest in hybrid and electric vehicles. This study presents an innovative approach for consumers and decision-makers to choose the best electric car alternatives. SD and MULTIMOORA, multi-criteria-decision-making techniques, were used as methods. The first 2 important criteria in the evaluation made with SD are the vehicle’s torque and DC charging time. The last 2 criteria of least importance are range and top speed. In the ranking of alternatives with MULTIMOORA, Hyundai Kona 150kW is the first alternative and Renault-ZOE is the fifth alternative. The study is innovative due to the criteria for choosing electric cars and the evaluation of current alternatives. Therefore it falls within the scope of being a pioneer for future studies.